ASME 2012 Summer Bioengineering Conference, Parts a and B 2012
DOI: 10.1115/sbc2012-80199
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Vertebra Stiffness in the Finite Element Analysis of the Intervertebral Disc

Abstract: Spine finite element models are an essential tool to study the degeneration of the intervertebral disc (IVD). Due to the complex geometry of the vertebras, the anisotropy and heterogeneity of the tissues, and the contact and material nonlinearities [1], spine models demand high computational resources. Considering the relatively low stiffness of the IVD compared to that of the vertebrae, we hypothesized that finite element stress and stress distributions of the IVD do not change substantially if the vertebras … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…30 These papers have shown that these simplifications have little influence over the final results, for instance, the maximum stress in the annulus fibrosus and the intradiscal pressure only changed about 2% when compared to the results of an elastic model for the bones and endplates. 28…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…30 These papers have shown that these simplifications have little influence over the final results, for instance, the maximum stress in the annulus fibrosus and the intradiscal pressure only changed about 2% when compared to the results of an elastic model for the bones and endplates. 28…”
Section: Discussionmentioning
confidence: 99%
“…With respect to the simplification of the endplates as rigid bodies, this assumption has been adopted in models reported by Dı´az et al, 28 Moramarco et al, 29 and Cegon˜ino et al 30 These papers have shown that these simplifications have little influence over the final results, for instance, the maximum stress in the annulus fibrosus and the intradiscal pressure only changed about 2% when compared to the results of an elastic model for the bones and endplates. 28…”
Section: Discussionmentioning
confidence: 99%